Evaluasi Laik Hygiene Sanitasi di ToBe Kitchen Jatimakmur Bekasi - Nurdini, Dahlia; Siregar, Bulan Anisha (Anakes : Jurnal Ilmiah Analis Kesehatan, 2024)
Sanitation is an effort to create and maintain healthy and healthy food conditions from the dangers of biological, chemical, and other contamination. Food sanitation Hygiene is a health effort to maintain and protect the cleanliness of the food environment where it is sold so that it does not cause health problems. This research aims to determine the evaluation of Hygiene and sanitation at ToBe Kitchen catering. This research method uses the Environmental Health Inspection Form (IKL). The results of this research show that ToBe Kitchen catering is located free from flooding, the location is free from pollution and is free from vector sources and there are no disease-carrying animals, there is clean drainage, there are no water blockages. The ceiling in the outside area does not have holes but there are sawings. The entrance door has a flat design, can close tightly, and leads to the outside, the door is always closed. It has air ventilation, and anti-insect screens and uses an exhaust air conditioner. The results of the evaluation of the implementation of sanitation hygiene in Tobe Kitchen show a score of 88.2 out of the maximum 100 certification standards for food service/catering service sanitation, which means that it meets the requirements of the Republic of Indonesia Minister of Health Regulation No. 14 of 2021.  Key words  : Hygiene sanitasi, catering, food safety